2020
DOI: 10.3390/sym12101712
|View full text |Cite
|
Sign up to set email alerts
|

EEG Resting Asymmetries and Frequency Oscillations in Approach/Avoidance Personality Traits: A Systematic Review

Abstract: Background: Brain cortical activity in resting electroencephalogram (EEG) recordings can be considered as measures of latent individual disposition to approach/avoidance behavior. This systematic review aims to provide an updated overview of the relationship between resting EEG cortical activity and approach/avoidance motivation personality traits. Methods: The review process was conducted according to the PRISMA-Statement, using PsycArticles, MEDLINE, Scopus, Science Citation Index, and Research Gate database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 188 publications
(687 reference statements)
1
14
0
Order By: Relevance
“…When changes in affect involve depressed mood, they often reflect the “approach-avoidance” paradigm for analyzing human personalities and behavior [ 9 ]. This widely-applied behavioral paradigm, originated in the 1930s by Kurt Lewin, one of the founders of modern social psychology, is based on the human tendency to assign value to outcomes specifically distinguishing between people who “approach” desired outcomes and are associated with positive affective states versus those who “avoid” negative outcomes and are associated with negative affective states [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…When changes in affect involve depressed mood, they often reflect the “approach-avoidance” paradigm for analyzing human personalities and behavior [ 9 ]. This widely-applied behavioral paradigm, originated in the 1930s by Kurt Lewin, one of the founders of modern social psychology, is based on the human tendency to assign value to outcomes specifically distinguishing between people who “approach” desired outcomes and are associated with positive affective states versus those who “avoid” negative outcomes and are associated with negative affective states [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations tempting to define the relationship between brain activity and personality focused on resting-state and connectivity as the potential explanatory factors. Several studies have suggested an interrelation between personality traits and patterns of whole brain resting state functional connectivity 7 , 8 , although these results have been challenged (for review see 9 ). By contrast, it is generally accepted that individual differences in cognitive performance are mediated by differences in dynamical neural systems and brain-wide interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Neural oscillations in the alpha range (8)(9)(10)(11)(12) can be observed at any site of the scalp overlying the brain, and are, generally, inversely related to activation level of the underlying cerebral cortex [1]. A low alpha wave voltage is observed when eyes are open and cortical regions are actively processing information [2].…”
Section: Background and Introductionmentioning
confidence: 99%
“…When changes in affect involve depressed mood, they often reflect the "approach-avoidance" paradigm for analyzing human personalities and behavior [9]. This approach underscores the human tendency to assign value to outcomes specifically distinguishing between people who "approach" desired outcomes and are associated with positive affective states versus those who "avoid" negative outcomes and are associated with negative affective states.…”
Section: Background and Introductionmentioning
confidence: 99%
See 1 more Smart Citation